Eating disorders among athletes: systematic review - Minarík, P.; Suchý, J.; Papežová, H. (Slovak Journal of Sport Science, 2024)
Eating disorders in the sports community are increasingly common, yet still considerably hidden diseases. Over the past decades, studies have shown a higher prevalence of eating disorders among athletes than in the general population. The risk of suffering an eating disorder differs in relation to gender, characteristics, and sports categories. The review article summarizes the available information on eating disorders in relation to endurance sports. The author also categorizes and identifies the risk factors leading to an eating disorder, common for both the general population and athletes.